Copper Cobalt Magnetic Ceramic Materials Characterization at Terahertz Frequencies - Boss,Alan Fernando Ney (2017)
ABSTRACT: This study presents the complex index of refraction and the complex permittivity of a magnetic ceramic material made of copper, cobalt, and iron oxides. The index of refraction and the extinction coefficient of the CuCo-ferrite exhibit an almost frequency independent behavior and were averaged to n = 3.62 ± 0.05 and k = 0.06 ± 0.02, respectively, over the frequency range from 0.2 to 1 THz. The corresponding complex permittivity was ε' = 13.12 ± 0.35 for the real part and ε'' = 0.46 ± 0.15 for the imaginary one. The absorption coefficient and the transmittance of the CuCo-ferrite were also determined. The absorption coefficient exhibits a dip at ~0.35 THz, which corresponds to a peak in transmittance at this frequency. The impact of the observations on the potential realization of novel THz electronic devices is discussed.